Development and Validation of Four-Tier Disgnoastic Instrument for Chemical Equilibrium - Nuchrurita Rosida; Hayuni Retno Widarti; Rizki Amelia (Jurnal Pendidikan Sains, 2021)
Abstract: Misconceptions can affect students' understanding. Identifying misconceptions is an important first step in gaining an understanding of student learning. One of the instruments that can be used to diagnose student misconceptions is a four-tier diagnostic instrument. This study aims to develop a four-tier diagnostic instrument on the material of chemical equilibrium. The final product produced is in the form of 20 multiple choice questions at four-tier. The resulting test questions are valid and reliable with a reliability score of 0.77. This shows that a four-tier diagnostic instrument on chemical equilibrium material can be used to diagnose student misconceptions.Abstrak: Miskonsepsi dapat berpengaruh pada pemahaman siswa. Identifikasi miskonsepsi merupakan Langkah awal untuk mendapatkan pemahaman tentang pembelajaran siswa. Salah satu instrumen yang dapat digunakan untuk mendiagnosis miskonsepsi siswa adalah instrumen diagnostik four-tier. Penelitian ini berujuan untuk mengembangkan instrumen diagnostik four-tier pada materi kesetimbangan kimia. Produk akhir yang dihasilkan berupa 20 soal pilihan ganda empat tingkat. Soal tes yang dihasilkan valid dan reliabel dengan skor reliabilitas sebesar 0,77. Hal ini menunjukkan bahwa instrumen diagnostik four-tier pada materi kesetimbangan kimia dapat digunakan untuk mendiagnosis miskonsepsi siswa.